Periodontal Vaccines: Boon or Mere Promise in Modern Dentistry? - Chhavi Khanna; Anchal Sood; Swantika Chaudhry; Harsukhman Kaur; Ankita Nayyar; Priyanka Pawar (Oral Sphere Journal of Dental and Health Sciences, 2026)
Periodontal disease is a chronic inflammatory disorder resulting from the dynamic interplay of pathogenic bacteria within the oral microbiota and host defense, ultimately leading to alveolar bone loss, tooth mobility, and tooth exfoliation. Conventional periodontal treatments (mechanical debridement and adjunctive antimicrobial agents) essentially control established disease, without offering lifelong protective immunity against relevant periodontopathogens. Periodontal vaccination is a new immunotherapeutic approach for inducing the host to generate an immune response toward certain bacterial virulence factors so that colonization and tissue destruction of periodontopathic bacteria in hosts are inhibited. Diverse kinds of vaccines, such as whole cell, subunit, recombinant protein, DNA and conjugate vaccines have been studied for their potential to elicit humoral and cellular immune responses. Preclinical trials in animal models have shown some positive outcomes, including reduction of bacterial load, inhibition of alveolar bone loss, and systemic as well as mucosal immune responses. Gingipain subunit and fimbrial Porphyromonas gingivalis DNA vaccines have provided particularly encouraging results. However, limitations such as the polymicrobial nature of periodontitis, interindividual differences in immune responses, safety issues and lack of human clinical trials still exist. These limitations can be potentially overcome by focusing on the mucosal Sdelivery systems, nanoparticle-based vaccines, multivalent formulations and personalized immunotherapy in future studies. Periodontal vaccination is a novel concept of preventive dentistry, which shifts the current treatment model to prophylactic methods based on immune-mediated disease prevention and life-long maintenance of periodontal as well as overall health.